2015
DOI: 10.1111/asj.12444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lysozyme levels on growth performance, intestinal morphology, non‐specific immunity and mRNA expression in weanling piglets

Abstract: The aim of the present study was to determine the effect of dietary lysozyme levels on growth performance, gut health and non-specific immunity of weanling piglets. A total of 150 weanling piglets were allocated to six treatments. The piglets were fed the same basel diet supplemented with 0, 30, 60, 90 and 120 mg/kg lysozyme as well as antibiotics for 28 days. From day 14 to day 28 of dietary treatment, piglets fed 90 mg/kg lysozyme had greater average daily gain than piglets fed control diet. During the whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Antibiotics have been used as growth promoters by improving feed efficiency for more than 50 years. A series of studies have proven the beneficial effects of dietary supplementation of lysozyme on growth performance of pigs at different stages of growth, including 10‐day‐old pigs, nursery pigs, weaned pigs and 6‐week‐old pigs . The current study showed that growing pigs fed with 100 mg kg −1 lysozyme had a similar or even better feed efficiency than pigs fed with colistin sulfate ( P > 0.05).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Antibiotics have been used as growth promoters by improving feed efficiency for more than 50 years. A series of studies have proven the beneficial effects of dietary supplementation of lysozyme on growth performance of pigs at different stages of growth, including 10‐day‐old pigs, nursery pigs, weaned pigs and 6‐week‐old pigs . The current study showed that growing pigs fed with 100 mg kg −1 lysozyme had a similar or even better feed efficiency than pigs fed with colistin sulfate ( P > 0.05).…”
Section: Discussionmentioning
confidence: 50%
“…Lysozyme can take part in the natural defence mechanism in Gram‐positive bacteria and perhaps indirectly affect Gram‐negative bacteria . It was proven that lysozyme could partially replace antibiotics as an important non‐specific immune component . Furthermore, Ginsburg found that lysozyme has many other biological functions, including regulation of inflammatory response, and antiviral and antitumor activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations